English Creek Native Tree and Plant Tour - Michael G. Andreu; Melissa H. Friedman; Mary E. Thornhill (EDIS)
FOR200, a 3-page fact sheet by Michael G. Andreu, Melissa H. Friedman, and Mary E. Thornhill, Describes the English Creek Preserve Native Tree and Plant Tour, with instructions for downloading and printing out a guidebook designed for use along the raised boardwalk trail, although it can also be used to identify trees and plants outside the preserve. Published by the UF School of Forest Resources and Conservation, October 2008.